2017
DOI: 10.1158/0008-5472.can-17-1353
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Heterogeneity of Circulating Tumor Cells Informs Clinical Decisions between AR Signaling Inhibitors and Taxanes in Metastatic Prostate Cancer

Abstract: The heterogeneity of an individual patient’s tumor has been linked to treatment resistance, but quantitative biomarkers to rapidly and reproducibly evaluate heterogeneity in a clinical setting are currently lacking. Using established tools available in a CAP-accredited and CLIA-certified clinical laboratory, we quantified digital pathology features on 9,225 individual circulating tumor cells (CTCs) from 179 unique metastatic castration-resistant prostate cancer (mCRPC) patients to define phenotypically distinc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 49 publications
6
88
0
1
Order By: Relevance
“…This is consistent with our recent report in which we examined CTC phenotypic heterogeneity indices in the same second line or greater treatment decision context and found that higher CTC heterogeneity was also associated with superior outcome on taxanes over ARS inhibitors. 28 Evidence of subclonal CTC genomics of AR-dependent and AR-independent signaling drivers co-occuring within the same patient sample were also observed in this study 28 , further supporting the concept that multiple mechanisms of resistance co-occur. Importantly, additional biomarkers to further stratify differential mCRPC patient survival by therapy are needed and should follow a similar stepwise validation process as the nuclear-localized AR-V7 assay.…”
Section: Discussionsupporting
confidence: 79%
“…This is consistent with our recent report in which we examined CTC phenotypic heterogeneity indices in the same second line or greater treatment decision context and found that higher CTC heterogeneity was also associated with superior outcome on taxanes over ARS inhibitors. 28 Evidence of subclonal CTC genomics of AR-dependent and AR-independent signaling drivers co-occuring within the same patient sample were also observed in this study 28 , further supporting the concept that multiple mechanisms of resistance co-occur. Importantly, additional biomarkers to further stratify differential mCRPC patient survival by therapy are needed and should follow a similar stepwise validation process as the nuclear-localized AR-V7 assay.…”
Section: Discussionsupporting
confidence: 79%
“…Taking in account CSC properties such self-renewal, tumorinitiating and therapy resistance, CSC-related signatures can be used in clinical practice for the different purposes, for [60,91,219] AR-(primary PC) or AR-/+ (CRPC) [3,11,125,220] AR-or AR+ [221][222][223][224][225] AR-or AR+ [226] AR-or AR+ [227,228] Anrogen dependence Primary PC: Yes CRPC: No [66,229] No [3,28,55,220] Yes / No [221,230,231] Yes / No [228] Yes / No [228] PSA expression…”
Section: Pcscs and Clinical Applicationmentioning
confidence: 99%
“…Yes [246] Yes [3,32,61,62,115,219,235,236] Yes [222,224,225,230,233,247] Yes [226,228,234] Yes [243,244] Cellular state…”
Section: Heterogeneitymentioning
confidence: 99%
“…One other interesting finding in the PROPHECY study was the higher phenotypic heterogeneity of CTCs that was observed in AR-V7(+) versus AR-V7(–) cases (63% vs. 14%, respectively). CTC phenotypic heterogeneity has previously been correlated with lack of response to ARSi drugs, (10) and may reflect a subset of clinically aggressive CRPC with AR-low or AR-negative CTCs. Since the PROPHECY study is still active, results of the sequential treatments with taxanes and other biomarker analyses are ongoing so we can better understand the role of these possible biomarkers.…”
mentioning
confidence: 96%